Early lipogranuloma formation after foreign material injection to the face - Karakol, Percin; Sezgiç, Melihcan (Journal of Surgery and Medicine, 2020)
Aging is a physiological process that progresses both physically and mentally. In today's conditions, there are medical devices and cosmetic procedures that support the external appearance and make the person feel good socially in order to age well. Over the years, thanks to the advancing technology, different solutions have been developed to compensate the loss of facial volume due to aging. Although the use of dermal fillers increases with each passing year, their excessive costs, and the need for periodic repetition force people to seek different and unhealthy solutions. In this study, we present a 32-year-old female patient who was injected with egg white in both nasolabial folds and presented with widespread redness and tenderness on the face. Surgical excision was performed after systemic corticosteroid therapy. The patient's granulomas excised from the mouth were reported as lipogranuloma by the pathology department. The frequency of foreign substance injections for cosmetic purposes has increased in recent years. Early diagnosis and follow-up is critical in the treatment of these cases.